Adaptive management in wildlife conservation - Organ, John; Decker, D.J.; McDonald, J.E.; Riley, Shawn; Mahoney, S.P. (The Wildlife Society Techniques Manual, 2012)
Adaptive management in wildlife conservation emerged from the wildlife profession's search for better solutions to increasingly complex conservation challenges. Adaptive management is an effective process for wildlife managers to employ to (1) deal with uncertainty in the management system, (2) learn from their management actions, and (3) achieve desired results. Being adaptable or flexible in your management approach is not the same as managing adaptively or conducting adaptive management. Adaptive management requires adhering to a stepwise process and fully executing each step. A critical step is rigorous monitoring and assessment of management interventions. Without this, wildlife managers cannot achieve the essence of adaptive management, which is the explicit goal of learning more about the management system after each management action.

Collaborative geomatics and the Mushkegowuk Cree First Nations: Fostering adaptive capacity for community-based sub-arctic natural resource management - McCarthy, Daniel D. P.; Whitelaw, Graham S.; Anderson, Scott; Cowan, Donald; McGarry, Fred; Robins, Anthony; Gardner, Holly L.; Barbeau, Christine D.; Charania, Nadia A.; General, Zachariah; Liedtke, Jeff; Sutherland, Celine; et al. (Geoforum, 2012)
The remote First Nation (FN) communities of the Mushkegowuk Territory on the west coast of James Bay, Ontario, Canada are currently facing increased development pressures and the imposition of a government land use planning process. The land use planning process is mandated in the Far North Act (received Royal Assent on September 23, 2010). There is a need for capacity enhancement for community-based natural resource planning and management in the Territory. A number of frameworks are emerging for addressing change brought on by resource development and building resilience to such change at the community level. Among these include the concept of adaptive capacity. In collaboration with FN community leaders, we explored the use of “collaborative geomatics” tools to foster adaptive capacity. Our action research suggests that collaborative geomatics technologies should enhance the Mushkegowuk First Nations’ adaptive capacity to address environmental and policy change by allowing them to collect and manage data collaboratively (e.g., traditional environmental knowledge, western science) to create opportunities for innovative community development, including natural resource development and management.
Keywords: Adaptive capacity; Collaborative geomatics; Community development; Cree communities; Land use plans

Complexity, Adaptation, and Results - Barder, Owen; Ramalingam, Ben (Center For Global Development, 2012)
In the last of a series of three blog posts looking at the implications of complexity theory for development, Owen Barder and Ben Ramalingam look at the implications of complexity for the trend towards results-based management in development cooperation. They argue that is a common mistake to see a contradiction between recognising complexity and focusing on results: on the contrary, complexity provides a powerful reason for pursuing the results agenda, but it has to be done in ways which reflect the context. In the 2012 Kapuscinski lecture Owen argued that economic and political systems can best be thought of as complex adaptive systems, and that development should be understood as an emergent property of those systems. As explained in detail in Ben’s forthcoming book, these interactive systems are made up of adaptive actors, whose actions are a self-organised search for fitness on a shifting landscape. Systems like this undergo change in dynamic, non-linear ways; characterised by explosive surprises and tipping points as well as periods of relative stability. If development arises from the interactions of a dynamic and unpredictable system, you might draw the conclusion that it makes no sense to try to assess or measure the results of particular development interventions. That would be the wrong conclusion to reach. While the complexity of development implies a different way of thinking about evaluation, accountability and results, it also means that the ‘results agenda’ is more important than ever.
Keywords: IMPORTANT

Teaming: how organizations learn, innovate, and compete in the knowledge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and promoting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those organizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible team-like entities. The pace of change and the fluidity of most work structures means that it's not really about creating effective teams anymore, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encompass are able to learn. The problem is teams, and other dynamic groups, don't learn naturally. Edmondson outlines the factors that prevent them from doing so, such as interpersonal fear, irrational beliefs about failure, groupthink, problematic power dynamics, and information hoarding. With Teaming, leaders can shape these factors by encouraging reflection, creating psychological safety, and overcoming defensive interpersonal dynamics that inhibit the sharing of ideas. Further, they can use practical management strategies to help organizations realize the benefits inherent in both success and failure. Presents a clear explanation of practical management concepts for increasing learning capability for business results Introduces a framework that clarifies how learning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it well Includes case-study research on Intermountain healthcare, Prudential, GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Children's Hospitals, among others Based on years of research, this book shows how leaders can make organizational learning happen by building teams that learn.

Broadening the range of designs and methods for impact evaluations - Stern, Elliot; Stame, Nicoletta; Mayne, John; Forss, Kim; Davies, Rick; Befani, Barbara (DFID, 2012)

The Implications of Complexity for Development - Barder, Owen (2012)
In this lecture, adapted from his May 2012 Kapuściński Lecture, Owen Barder explores the implications of complexity theory for development policy. He explains how traditional economic models have tried and failed to understand why some countries have managed to improve living standards while other countries have not.
Keywords: IMPORTANT

Narrowing the climate information usability gap - Lemos, Maria Carmen; Kirchhoff, Christine J.; Ramprasad, Vijay (Nature Climate Change, 2012)
Climate-change-related risks pose serious threats to the management of a wide range of social, economic and ecological systems. Managing these risks requires knowledge-intensive adaptive management and policy-making actively informed by scientific knowledge, especially climate science1. However, potentially useful climate information often goes unused1,2. This suggests a gap between what scientists understand as useful information and what users recognize as usable in their decision-making. We propose a dynamic conceptual model to address this gap and highlight strategies to move information from useful to usable to reduce climate-related risks.